ANALISIS CAMPUR KODE PADA TUTURAN PEWARA DALAM ACARA “PESTA WIRAUSAHA BERAKSI UNTUK NEGERI DIMULAI DARI DIRI” - Suci Rahmani; Nita Nuraeni; Aditya Permana (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
In this study discussed the problem of mixed code speech circulating in the wider community, especially in entrepreneurial parties "acting for the country starting from the self". So that the researcher formulates the problem as follows 1) how to mix the speech code spoken by the instructor at the entrepreneurial party event, and 2) the transcription of the speech or speech that has been recorded. This study aims to see and know the mixed code speech spoken by the instructor at the event. This study uses a qualitative description method that describes the transcription of recorded speech into written form and analyzes the existence of a mixed code. This study obtained results namely pewara using everyday Indonesian, three Sundanese words, English, and Javanese in the use of speech such as regional languages that are in accordance with the scope of the community that understands language, and English which is also easily understood by partners or recipients of speeches in the entrepreneurial party. Even this result found code cords including word division of numeralia, word rephrases, word shortening, word repetition, noun, question word, greeting word, particle word, verb, adjective, the combination of words, and news sentences in the speaker's utterance.